Local and systemic responses to SARS-CoV-2 infection in children and adults. - Yoshida, Masahiro; Worlock, Kaylee B; Huang, Ni; Lindeboom, Rik GH; Butler, Colin R; Kumasaka, Natsuhiko; Dominguez Conde, Cecilia; Mamanova, Lira; Bolt, Liam; Richardson, Laura; Polanski, Krzysztof; Madissoon, Elo; et al. (Springer Science and Business Media LLC, 2022)
It is not fully understood why COVID-19 is typically milder in children1-3. Here, to examine the differences between children and adults in their response to SARS-CoV-2 infection, we analysed paediatric and adult patients with COVID-19 as well as healthy control individuals (total n = 93) using single-cell multi-omic profiling of matched nasal, tracheal, bronchial and blood samples. In the airways of healthy paediatric individuals, we observed cells that were already in an interferon-activated state, which after SARS-CoV-2 infection was further induced especially in airway immune cells. We postulate that higher paediatric innate interferon responses restrict viral replication and disease progression. The systemic response in children was characterized by increases in naive lymphocytes and a depletion of natural killer cells, whereas, in adults, cytotoxic T cells and interferon-stimulated subpopulations were significantly increased. We provide evidence that dendritic cells initiate interferon signalling in early infection, and identify epithelial cell states associated with COVID-19 and age. Our matching nasal and blood data show a strong interferon response in the airways with the induction of systemic interferon-stimulated populations, which were substantially reduced in paediatric patients. Together, we provide several mechanisms that explain the milder clinical syndrome observed in children.
Keywords: Article; /631/250/254; /631/337/2019; /631/208/514/1949; /631/326/596/4130; /13/51; /38/91; article